Duration of effectiveness of Botulinum toxin type A in excessive gingival display: a systematic review and meta-analysis - Taísa Figueiredo Chagas; Natalia Valli de Almeida; Cinthia Oliveira Lisboa; Daniele Masterson Tavares Pereira Ferreira; Claudia Trindade Mattos; José Nelson Mucha (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract Botulinum toxin type A is effective in reducing excessive gingival display caused by hyperfunctional upper lip elevator muscles; however, this effect is transient. This study aimed to determine the duration of the effectiveness of botulinum toxin type A on a gummy smile. A systematic search was conducted using Medline (PubMed), Scopus, and Web of Science electronic databases, from 1970 to March 2017 with no language restriction; the search included studies evaluating adult patients with excessive gingival display who were treated with botulinum toxin and were followed-up for at least 3 months. OpenGrey and Clinical Trial Registry were also consulted. Quality assessment was applied to determine the level of evidence and bias, and a meta-analysis was performed. Of 2181 full texts, 71 were obtained, with 3 prospective studies meeting the selection criteria. The gingival display was significantly reduced to baseline with 2, 4, and 8 weeks of treatment. The gingival display considerably reduced at the baseline-2-week comparison (-4.44 mm using raw data and-4.05 mm using the standard difference) and increased throughout the weeks of follow-up. There is scant evidence to determine the duration of the effectiveness of toxin type A on a gummy smile. The effect tends to be stable until at least 8 weeks of follow-up, and the gingival exposure may not return to baseline within 12 weeks of follow-up. Well-designed randomized clinical trials with a minimum of 6 months of follow-up are necessary to strengthen the evidence.